Investigation of the thermal parameters of an aluminum heater with nanoporous alumina - Ekaterina N. Muratova; Vyacheslav A. Moshnikov; Katsiaryna V. Chernyakova; Igor A. Vrublevsky (Modern Electronic Materials, 2020)
An important task faced in the industry of permanently installed heating systems addressed by a large number of manufacturers is power saving. Heating systems may have variegated designs, yet there are basic design requirements, i.e., high operational reliability, resource saving, environmental resistivity and stability of electric parameters. The key component of any heating unit is the heater. Flat resistive heaters have found wide application in heating units aimed at sustaining healthy indoor microclimate, maintaining preset process parameters on industrial premises, as well as in anti-icing systems, agriculture and general industry. We studied the thermal parameters of flat aluminum heating units containing carbon fiber ribbon heaters. To ensure the required insulation of the heater from the metallic base plate, the aluminum surface had a 20 mm thick porous aluminum oxide layer. The ends of the carbon fiber were metalized with a layer of copper for further soldering upon integration into the electric heating unit assembly. The electrical resistance of the heater with a carbon fiber was 60 Ohm. The propagation of heat flows inside a plate of aluminum with nanoporous aluminum oxide was studied using thermal imaging measurements. Temperatures on the surface of the aluminum heater cover and on the opposite heat emitting side were shown as a function of heating time. The experimental results suggest that the heat generated by the linear carbon fiber heater distributes rapidly in the entire bulk of the aluminum heater plate. This indicates a high heat conductivity of the heater aluminum base plate whose parameters provide for the required thermal parameters of the heating unit.